The effects of proteins released from silk mat layers on macrophages - Ju-Won Kim; You-Young Jo; Hae Yong Kweon; Dae-Won Kim; Seong-Gon Kim (Maxillofacial Plastic and Reconstructive Surgery, 2018)
Abstract Background The objective of this study was to evaluate the changes in gene expression after incubation of cells with proteins released from different silk mat layers. Methods A silk cocoon from Bombyx mori was separated into four layers of equal thickness. The layers were numbered from 1 to 4 (from the inner to the outer layer). The proteins were released by sonication of a silk mat layer in normal saline. The concentration of proteins was determined by spectrophotometry. They were incubated with RAW264.7 cells, and changes in the expression of genes were evaluated by cDNA microarray analysis and quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR). Results Layer 1 and 4 groups had higher protein concentrations compared to those in layer 2 and 3 groups. The genes associated with inflammation and angiogenesis showed significantly higher expression in layer 1 and 4 groups. The results of qRT-PCR were in agreement with those of the cDNA microarray analysis. Conclusions The silk mat from the middle portion of the silkworm cocoon yielded a lower protein release and caused an insignificant change in the expression of genes that are associated with inflammation and angiogenesis.